Measuring Welfare Equality: Essential Factors Supporting Inclusive Economic Growth In West Nusa Tenggara Province 2021-2025 - Siti Fatimah; Haryanto, Tri; Solihin, Achmad (Universitas Udayana, 2025)
Inclusive economic growth is a new paradigm in measuring the success of economicdevelopment in the current era. This study aims to analyze and identify the essentialfactors that support inclusive economic growth in the regency/city of NTB Provincefor the next five years (2021-2025). This research uses the semi-averaging method incalculating data projections for 2024-2025. The data analysis technique used in thisresearch is panel data regression. The findings of this study indicate that over the nextfive years (2021-2025), inclusive economic growth in NTB regencies/cities is predictedto be in the medium category. The findings of this study also show that a decrease inpoverty levels, income inequality, and unemployment rates are important factors thatsupport inclusive economic growth in Regency / City in NTB Province in the next fiveyears (2021-2025).